The predictors of financial well-being and its impact on overall well-being: the case of Portugal - Dias, Raquel Ferreira (2021)
Although overall well-being is a well study phenomenon, financial well-being only recently has taken interest in the research field. Accordingly, the aim of this study is to understand the relation between financial well-being, its predictors (financial status, financial behaviour, financial knowledge and financial attitudes) and overall well-being. Additionally, hypotheses were tested with age, gender, household income and area of residence. It was used the quantitative method to gather the data, and to analyse it, the SPPS through linear regression analysis, mediation analysis, independent t-test and an anova test. Regarding the results, the financial status is the only positive and significant impactor on financial well-being and the latter has a significant positive relation with overall well-being. It was also found that financial well-being was a mediator between financial status and overall well-being. Overall, the other predictors did not show a significant effect. Moreover, higher household incomes contribute to increase the financial well-being. Plus, I found that there were differences in financial wellbeing between groups. For example, the older you get does not necessarily implies a higher financial satisfaction. Overall, men appear to have a higher financial well-being than women. In sum, these results show a multidisciplinary concept of overall well-being and that individuals prioritise financial security over the other components. In terms of practical implications, this research is relevant because it highlights the evidence of financial status’ importance in predicting financial well-being, as well as the role of household income for individual financial satisfaction.